Against the current and into the light : performing history and land in Coast Salish territories and Vancouver's Stanley Park - Couture, Selena (McGill-Queen's native and northern series, 2019)
"Performance embodies knowledge transfer, cultural expression, and intercultural influence. It is a method through which Indigenous people express their relations to land and continuously establish their persistant political authority. But performance is also key to the misrepresentation of Indigenous peoples in settler colonial societies. Against the Current and Into the Light challenges dominant historical narratives of the land now known as Stanley Park, exploring performances in this space from the late nineteenth century to the present. Selena Couture engages with knowledge held in an endangered Indigenous language's place names, methods of orientation in space and time, and conceptions of leadership and respectful visiting. She then critically engages with narratives of Vancouver history created by the city's first archivist, J.S. Matthews through his interest in Lord Stanley's visit to the park in 1889. Matthews organized several public commemorative performances on this land from the 1940s to 1960, resulting in the iconic yet misleading statue of Lord Stanley situated at the park's entrance. Couture places Matthews's efforts at commemoration alongside continuous political interventions by Indigenous people and organizations such as the Native Brotherhood of British Columbia, while also responding to contemporary performances by Indigenous women in Vancouver which present alternative views of history. Using the metaphor of eddies of influence--motions that shape and are shaped by obstacles in their temporal and spatial environments--Against the Current and Into the Light reveals how histories of places have been created, and how they might be understood differently in light of Indigenous resurgence and decolonization."--